The Influence Of Recruitment, Training, And Work Motivation In Improving Employee Performance At PT. Perkasa Internusa Mandiri - Siagian, Jonatan Pebrianto; Insan, Muhammad Yalzamul; Yanti, Eli Delvi (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of recruitment, training, and work motivation on employee performance at PT. Perkasa Internusa Mandiri. This study uses a quantitative approach with a survey method of 80 employees which is also used as a sample. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS program. The results showed that recruitment had a regression coefficient (B) of 0.187 with a t-value of 1.909 and a significance of 0.060, so that it had a positive but insignificant effect on employee performance. The training has a regression coefficient (B) of 0.538 with a t-value of 4.821 and a significance of 0.000, which means that it has a positive and significant effect on employee performance. Work motivation has a regression coefficient (B) of −0.283 with a t-value of −2.968 and a significance of 0.004, so that it has a negative and significant effect on employee performance. The results of the simultaneous test showed an F value of 27.253 with a significance of 0.000, which indicates that recruitment, training, and work motivation together have a significant effect on employee performance. A determination coefficient value (R²) of 0.518 indicates that 51.8% variation in employee performance can be explained by the research model. Training is the most dominant variable in improving employee performance.